Prion pathogenesis is faithfully reproduced in cerebellar organotypic slice cultures. - Jeppe Falsig; Tiziana Sonati; Uli S Herrmann; Dino Saban; Bei Li; Karina Arroyo; Boris Ballmer; Pawel P Liberski; Adriano Aguzzi (PLoS Pathogens)
Prions cause neurodegeneration in vivo, yet prion-infected cultured cells do not show cytotoxicity. This has hampered mechanistic studies of prion-induced neurodegeneration. Here we report that prion-infected cultured organotypic cerebellar slices (COCS) experienced progressive spongiform neurodegeneration closely reproducing prion disease, with three different prion strains giving rise to three distinct patterns of prion protein deposition. Neurodegeneration did not occur when PrP was genetically removed from neurons, and a comprehensive pharmacological screen indicated that neurodegeneration was abrogated by compounds known to antagonize prion replication. Prion infection of COCS and mice led to enhanced fodrin cleavage, suggesting the involvement of calpains or caspases in pathogenesis. Accordingly, neurotoxicity and fodrin cleavage were prevented by calpain inhibitors but not by caspase inhibitors, whereas prion replication proceeded unimpeded. Hence calpain inhibition can uncouple prion replication from its neurotoxic sequelae. These data validate COCS as a powerful model system that faithfully reproduces most morphological hallmarks of prion infections. The exquisite accessibility of COCS to pharmacological manipulations was instrumental in recognizing the role of calpains in neurotoxicity, and significantly extends the collection of tools necessary for rigorously dissecting prion pathogenesis.